2020
DOI: 10.48550/arxiv.2007.04119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Solitons in the dark: non-linear structure formation with fuzzy dark matter

Mattia Mina,
David F. Mota,
Hans A. Winther

Abstract: We present the results of a full cosmological simulation with the new code SCALAR, where dark matter is in form of fuzzy dark matter, described by a light scalar field with a mass of m B = 2.5 × 10 −22 eV and evolving according to the Schrödinger-Poisson system of equations. In comoving units, the simulation volume is 2.5 h −1 Mpc on a side, with a resolution of 20 h −1 pc at the finest refinement level. We analyse the formation and the evolution of central solitonic cores, which are found to leave their impri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…A second special class of UBDM compact objects is formed by the process of spontaneous symmetry breaking, if this occurs during the normal course of thermal evolution of the Universe (as opposed to during the initial Very recently some authors have even found a different best-fit exponent [98,99], and numerical convergence may also play a part. The issue is not yet resolved at the time of writing.…”
Section: Miniclustersmentioning
confidence: 99%
“…A second special class of UBDM compact objects is formed by the process of spontaneous symmetry breaking, if this occurs during the normal course of thermal evolution of the Universe (as opposed to during the initial Very recently some authors have even found a different best-fit exponent [98,99], and numerical convergence may also play a part. The issue is not yet resolved at the time of writing.…”
Section: Miniclustersmentioning
confidence: 99%
“…Almost all of that body of work focuses on FDM with particle mass 𝑚 ∼ (10 −23 − 10 −22 ) eV/𝑐 2 , chosen such that the respective 𝜆 dB ∼ (1 − 10) kpc is large enough to expose the genuine different dynamics of (S)FDM, where quantum wave phenomena, such as coherent states or wave interference, are seen at galactic scales and beyond. More precisely, FDM simulations like those of Schive et al (2014), Schwabe, Niemeyer & Engels (2016), Mocz et al (2017) and Mina, Mota & Winther (2020) have revealed that halos, grown either in a static or expanding background, exhibit a core-envelope structure, where the coherent solitonic halo core is embedded into a highly dynamical halo envelope. Also, certain core-halo scaling relationships have been determined between core and the halo at large, although the results of simulations differ somewhat with respect to the exponents found, which has consequences for other observables, see Padilla et al (2021).…”
mentioning
confidence: 99%
“…This type of DM is more generally termed Fuzzy DM (FDM), because these particles can be regarded as "fuzzy" due to the Heisenberg uncertainty principle. Cosmological simulations have shown that FDM halos have solitonic cores, and approaches a NFW-like profile at larger radii [42,44,45,49,59]. Both simulations and cosmological data [3,26,27,29,31,34,57] suggest the mass of the ultra-light scalar particle in the FDM scenario to be around 10 −22 eV.…”
Section: Introductionmentioning
confidence: 98%